2017
DOI: 10.1016/j.chemosphere.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of triclosan on spatial displacement and local population decline of the fish Poecilia reticulata using a non-forced system

Abstract: Triclosan (TCS) is an emerging contaminant of concern in environmental studies due to its potential adverse effects on fish behavior. Since avoidance has been shown to be a relevant behavioral endpoint, our aims were: (i) to determine if TCS is able to trigger an avoidance response in Poecilia reticulata; (ii) to predict the population immediate decline (PID) caused by TCS exposure, by integrating lethality and avoidance responses; and (iii) to verify the overestimation of risk when mortality is assessed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
2
25
0
4
Order By: Relevance
“…Later, Moreira‐Santos et al () improved that system to be used with small fish, and Rosa et al () proposed an alternative static system, with no pump, thus preventing any influence of water flow on the displacement of organisms. This recent alternative of a static linear system has been widely described in studies of contamination‐driven spatial avoidance (Araújo et al , , , 2016b, 2014c; Vasconcelos et al ; Silva et al , ). Compartments forming the linear system can be manually constructed from 2 plastic bottles glued at their cut‐off bases using white silicon and connected at the mouths to create a multicompartmented system, or else borosilicate glass can be used, as described by Silva et al ().…”
Section: Nonforced Multicompartmented Exposure Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Moreira‐Santos et al () improved that system to be used with small fish, and Rosa et al () proposed an alternative static system, with no pump, thus preventing any influence of water flow on the displacement of organisms. This recent alternative of a static linear system has been widely described in studies of contamination‐driven spatial avoidance (Araújo et al , , , 2016b, 2014c; Vasconcelos et al ; Silva et al , ). Compartments forming the linear system can be manually constructed from 2 plastic bottles glued at their cut‐off bases using white silicon and connected at the mouths to create a multicompartmented system, or else borosilicate glass can be used, as described by Silva et al ().…”
Section: Nonforced Multicompartmented Exposure Systemsmentioning
confidence: 99%
“…A laboratory study using the fish P . reticulata showed that an immediate population decline of approximately 40% might occur due to avoidance (with no influence from mortality) at environmentally relevant triclosan concentrations (<2 μg L −1 ; Silva et al ). By using either acute or chronic responses, the integration of both forced and nonforced approaches might improve our understanding of the population decline expected to occur when organisms are exposed to and are able to detect contamination.…”
Section: Integrating Ecological Concepts To Improve Erasmentioning
confidence: 99%
“…This approach expands the concept of environmental disturbance beyond the traditional one based exclusively on the toxicity (and bioaccumulation) at the organism level. Evidence of contamination-driven spatial displacement (avoidance response) in non-forced exposure systems has been described for many organisms including fish (Moreira-Santos et al, 2008;Araújo et al, , 2018Silva et al, 2017Silva et al, , 2018, amphibians Vasconcelos et al, 2016), and invertebrate species (Lopes et al, 2004; exposed to different contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time as it allows the passage of the fish, the reduced opening avoids diffusion between the compartments. The difference between both examples is that in the first one (figure 3-A) there is a renewal of the solution in each chamber through peristaltic pumps, while the second is static (Figure 3 Generally, in aquatic ecosystems, there is dispersion / dilution of the pollutants released (López-Doval et al, 2017), forming a gradient of contamination. That is, avoidance can be estimated in an environment simulating real environmental conditions Rosa et al, 2008;.…”
Section: ~ 6 ~mentioning
confidence: 99%
“…A second problem (besides concentrations) that contributes to the lack of realism in ecotoxicological studies arises when exposure to contaminants is simulated assuming a homogeneous distribution of the contamination. In aquatic systems, contaminants often disperse, forming a dilution gradient, so the induced stress tends to be negatively correlated with the distance from the source of the contamination (Araújo et al, 2016a;López-Doval et al, 2017). In the case of mobile organisms, their displacement to locations distant from the contamination source prevents continuous exposure to contaminants.…”
Section: ~ 42 ~mentioning
confidence: 99%